Indonesian E-Commerce: Examining E-CRM, Browsing, Satisfaction and Loyalty - Suyanto, Suyanto; Rachbini, Widarto; Wulandjani, Harimurti; Grashinta, Aully; Rahmawati, Emi (International Review of Management and Marketing, 2024)
This research aims to investigate the influence of Electronic Customer Relationship Management (e-CRM), hedonic browsing, and utilitarian browsing on e-satisfaction and e-loyalty in online shopping in Indonesia. To investigate the associations between these variables, Structural Equation Modeling (SEM) analysis was performed using a quantitative study methodology and survey data from 962 respondents. The findings show a strong correlation between utilitarian browsing and e-satisfaction and e-loyalty, hedonic browsing and e-satisfaction, and e-satisfaction and e-loyalty. Nevertheless, there was no statistically significant correlation discovered between e-CRM and e-loyalty or e-satisfaction. The results highlight the significance of giving equal weight to hedonic and utilitarian elements of the virtual buying encounter in order to augment client contentment and allegiance. Furthermore, even though the findings did not conclusively confirm the efficacy of e-CRM techniques in affecting customer outcomes, managers ought to be aware of their potential influence on cultivating enduring customer connections.